OUTCOMES OF URETERORENOSCOPY WITH PNEUMATIC LITHOCLAST FOR URETERIC STONE MANAGEMENT AT A REGIONAL CENTER: A RETROSPECTIVE STUDY - SHAHZAD, I; MANZOOR, M; AWAN , KH; YOUSUF, MA; PATHAN, GM; KUMAR, S (Biological and Clinical Sciences Research Journal, 2024)
The management of ureteric stones has significantly evolved with the advancement of minimally invasive techniques. Ureterorenoscopy (URS) with pneumatic lithoclast has become favored due to its efficacy and safety, providing high success rates across various stone locations. Objective: To share our experiences and outcomes of treating ureteric stones using ureterorenoscopy and pneumatic lithoclast at our regional center. Methods: From 2014 to 2022, 220 patients with ureteral calculi at our regional center underwent 221 URS procedures using a pneumatic lithoclast. Preoperative evaluation included plain radiography, ultrasound scan, intravenous urography, and CT KUB. Postoperative assessments with plain film radiography and, if necessary, ultrasound or CT KUB were conducted immediately or a few days after the procedure. Results: The overall stone-free rate achieved was 95.4%. Specific success rates based on stone location were 88.4% for upper, 97% for middle, and 100% for lower ureteral stones. The primary cause of treatment failure, occurring in 4.5% of cases, was stone migration. Conclusion: Ureteroscopic intra-corporeal lithotripsy is a reliable and safe treatment modality for ureteric stones of various sizes and locations, demonstrating high efficacy when performed by experienced practitioners.